Identifying the gap in clinical skills: a pilot study investigating the use of clinical respiratory examination skills in practice. Issue 5 (3rd September 2021) - Kerzner, Sophia; Mao, Randi Q.; Patel, Janhavi Nikhil; Sreeraman, Shreyas; Profetto, Jason
ABSTRACT: There is a paucity of literature that explores whether students use clinical skills learned during medical school in practice. The study aimed to report on the most clinically relevant examination skills to focus on and increase student preparedness for clinical practice. We disseminated a 10-minute online anonymised survey to residents and physicians using an open recruitment strategy with convenience and snowball sampling. This survey sought to determine the practical use of respiratory exam skills. We conducted basic quantitative and descriptive content analysis to evaluate results. From a total of 161 respondents, 148 completed the entire survey. The majority of respondents found all 12 inspection skills to be useful in practice. Tracheal deviation was the only palpation skill found useful (68.63% useful). Auscultating for breath sounds was found to be unanimously useful, while all other percussion and auscultation skills were not found useful. In qualitative analysis, the major theme was that skills should be taught despite minimal use as they help teach disease pathophysiology, help in limited resource settings, and have usefulness in particular situations (e.g. traumas or different specialities). There is a discrepancy between the clinical skills taught to students and the ones actually used in practice. Despite this, there is still utility in teaching these skills to medical students. Rather than removing skills from the curriculum, a better avenue would be to emphasise manoeuvres that are clinically important to help guide preparation for clinical settings.